A STUDY TO COMPARE THE EFFECT OF CLOSED AND OPEN KINETIC CHAIN EXERCISE WITH KINESIO TAPING FOR PATELLO FEMORAL PAIN SYNDROME (International Journal of Physiotherapy, 2015)
Background: Patello femoral pain syndrome is dull, aching pain anterior to knee which frequently activity related may be present in one or both knees with difficulty in walking, running. The purpose of the study is to evaluate the effect of open kinetic chain exercise with Kinesio taping versus close kinetic chain exercise with kinesio taping for improving pain and functional mobility in subjects with unilateral patellofemoral pain syndrome.Methods: An Experimental study design, 30 subjects with unilateral patellofemoral pain were selected and randomized 15 subjects into each two groups. Group-A received Open Kinetic chain exercise with Kinesio taping while Group-B received Close kinetic chain exercises with kinesio taping. The duration of intervention was 2 weeks. Outcome measure such as Functional mobility was measured using a Kujala questionnaire and pain was measured using a VAS scale before and after two weeks of intervention.Results: Analysis using Independent ‘t’ test and Mann Whitney U test found that there is statistically significant difference with p